Antropologia da doenca e do doente: percepcoes e estrategias de vida dos tuberculosis. - Bertolli Filho, C. (My University, 1999)
The article examines how tuberculosis patients who were exiled to sanitarium-cities in the state of Sao Paulo reacted to the social representations assigned to them not only by the public at large but by medical workers as well. By evaluating memoirs and related documents from the perspective of the anthropology of disease and the diseased, it was possible to identify the network of signifieds created by the afflicted community.
The antropology of disease and the diseased: perceptions and life strategies adopted by tuberculosis patients
Keywords: Brazil; cultural anthropology; history; patient; patient participation; tuberculosis; Culture; History, 20th Century; Patient Participation; Patients; Tuberculosis